(untitled) (Research, Society and Development, 2025)
The present work aims to investigate the impact of carbohydrate supplementation on the athletic performance of runners. Running, as an endurance sport, demands high energy expenditure, with carbohydrates being the primary energy source during prolonged exercise. Through a comprehensive literature review, including studies published between 2014 and 2024, various nutritional strategies, carbohydrate types, recommended doses, and the role of gut training in efficient nutrient absorption were analyzed. The studies demonstrate that adequate carbohydrate supplementation significantly improves athletic performance, reduces muscle damage, and minimizes gastrointestinal discomfort. Additionally, strategies such as the consumption of multiple carbohydrate types (glucose and fructose), personalized intake based on intensity and duration of exercise, and proper post-training recovery are crucial for sports success. It is concluded that carbohydrate supplementation is essential for runners aiming to optimize performance and maintain physiological integrity during training and competitions.